2020
DOI: 10.1371/journal.pone.0237247
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of pneumococcal carriage in children 2 to 4 years of age in the winter seasons of 2017-2019 in Irbid and Madaba governorates of Jordan

Abstract: Streptococcus pneumoniae is one of the leading causes of death worldwide. It disseminates through colonizers and causes serious infections. Aims of this study are to determine pneumococcal carriage rate, resistance, serotype distribution, and coverage of pneumococcal conjugate vaccines from children attending day care centers from Irbid and Madaba in Jordan. Nasopharyngeal swabs were collected from day care centers (DCCs) of healthy Jordanian children 2-4 years of age from four regions of Madaba (n = 596), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Streptococcus pneumoniae is an infectious agent that causes invasive and non-invasive infections, especially in low-income countries with low or minimum vaccination rates [ 1 , 2 , 3 ]; it is an opportunistic human-adapted pathogen transmitted by the nasopharynx, which is an ecological reservoir for this bacterium, mainly during the first few months of life [ 4 ]. This NP carriage present in healthy children in rates between 20 and 40%, and it is influenced by different risk factors, including day care center attendance, the size of day care center, living in close contact with siblings, living in urban or rural areas, previous antibiotic consumption within one month before sample collection, cigarette smoking within family members, overcrowding in households, and socioeconomic factors [ 5 , 6 , 7 ]. Furthermore, this NP carriage is subject to genomic changes during natural colonization [ 8 ], and is acquired at approximately 4–6 months of age [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus pneumoniae is an infectious agent that causes invasive and non-invasive infections, especially in low-income countries with low or minimum vaccination rates [ 1 , 2 , 3 ]; it is an opportunistic human-adapted pathogen transmitted by the nasopharynx, which is an ecological reservoir for this bacterium, mainly during the first few months of life [ 4 ]. This NP carriage present in healthy children in rates between 20 and 40%, and it is influenced by different risk factors, including day care center attendance, the size of day care center, living in close contact with siblings, living in urban or rural areas, previous antibiotic consumption within one month before sample collection, cigarette smoking within family members, overcrowding in households, and socioeconomic factors [ 5 , 6 , 7 ]. Furthermore, this NP carriage is subject to genomic changes during natural colonization [ 8 ], and is acquired at approximately 4–6 months of age [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on the impact of vaccination on racial disparities of IPD incidence showed a high reduction after the introduction of PCV7 and PCV13 [ 18 ]. However, pneumococcal studies published for Jordan concentrated only on rural areas, especially where no PCVs were available [ 1 , 5 , 19 ]. Furthermore, Jordan is a mixture of cultures, especially after the Gulf and Syrian wars, in addition to being home to a large number of other nationalities and refugees.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance situation of the pneumococcal strains isolated from children colonizers was studied in other rural areas of Jordan previously. These rural areas were Ajlun in 2009-2010 with penicillin resistance rate of 84.0% (19), then was found to be 80.0% in 2014 for Wadi Alseer (1) as a rural area in the peripheries of Amman, then was found in the rural area of eastern Irbid with a rate of 86.3% in 2019 (5). Resistance rates found in this study for penicillin was found to be 95.8% as significantly higher (P< 0.05) than all rural areas tested before in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known as an opportunistic human-adapted pathogen transmitted by the nasopharynx as an ecological reservoir for this bacterium inhabiting the nasopharynx during the first few months of life (4). This NP-carriage is available in healthy children in rates between 20 to 40%, which is influenced by different risk factors including day care center attendance, size of day care center, living in close contact as siblings, living in urban or rural areas, previous antibiotic consumption within one month before sample collection, cigarette smoking, overcrowdings in households, and socioeconomic factors (5)(6)(7). Furthermore, NP-carriage is subject to genomic changes during natural colonization (8), and is acquired at approximately 4-6 months of age (1,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation